Consumer intentions, reactance and the marketing implications of policy induced mergers and acquisitions in financial services. Issue 3 (5th January 2022) - Mensah, Kobby; Madichie, Nnamdi O.; Mensah, Gilbert Kofi; Awini, Gideon
Abstract : Purpose: The purpose of this study is to establish, drawing upon the indirect effects of customer reactance from an emerging economy perspective, the marketing implications of policy induced Mergers and Acquisitions (M&A) in Financial Services. Design/methodology/approach: The study employed a quantitative research approach, relying on data from 517 customers of M&A banks in Ghana. Purposive sampling technique was used in selecting respondents for the study. Hypotheses were tested using a structural equation modelling. Findings: A positive and significant relationship between immersive marketing communication and consumer intention is revealed in the study. The presence of consumer reactance highly influenced the relationship. As a public policy tool, forced mergers and acquisitions was found to increase customer reactance. However, when customers are frequently engaged with relevant and consistent marketing communications through appropriate channels, such reactance would only be partial. Research limitations/implications: Although some of the information were collected, they were not the main focus of our analysis. We acknowledge, from the sample demographics perspective, the study did not consider certain other confounding factors that could influence customers' decisions to remain or switch such as customers' level of banking, type of account, income level, banking experiences in relation to service fees, online banking etc., as these could also potentially influence customers' reactance. Perhaps these may have to be considered in future studies. Social implications: When timely and relevant marketing communications are targeted at the customers who are directly impacted by the M&A process, they would experience reactance, but only partially. This has a range of marketing implications for policy-induced M&A and its impact on consumer intention, reactance and attitudes towards the new entity. Originality/value: The marketing of financial services literature has been silent on the implications of M&A from a policy induced perspective. This study, therefore, contributes to theory by highlighting that the "destruction" of brand value of the affected firms is relatively high in a policy induced M&A and thus increases the level of customer reactance. This is because a regulator enforced M&A, as public policy, usually generates high public interest and public discourse, leading to a heightened customer reactance. However, when immersive marketing communications are targeted at the customers directly impacted by the M&A, they would experience reactance, but only partially.